A multicenter study shows PTEN deletion is strongly associated with seminal vesicle involvement and extracapsular extension in localized prostate cancer. Issue 11 (4th May 2015) - Troyer, Dean A.; Jamaspishvili, Tamara; Wei, Wei; Feng, Ziding; Good, Jennifer; Hawley, Sarah; Fazli, Ladan; McKenney, Jesse K.; Simko, Jeff; Hurtado‐Coll, Antonio; Carroll, Peter R.; Gleave, Martin; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Loss of the phosphatase and tensin homolog (PTEN) tumor suppressor gene is a promising marker of aggressive prostate cancer. Active surveillance and watchful waiting are increasingly recommended to patients with small tumors felt to be low risk, highlighting the difficulties of Gleason scoring in this setting. There is an urgent need for predictive biomarkers that can be rapidly deployed to aid in clinical decision‐making. Our objectives were to assess the incidence and ability of PTEN alterations to predict aggressive disease in a multicenter study. METHODS We used recently developed probes optimized for sensitivity and specificity in a four‐color FISH deletion assay to study the Canary Retrospective multicenter Prostate Cancer Tissue Microarray (TMA). This TMA was constructed specifically for biomarker validation from radical prostatectomy specimens, and is accompanied by detailed clinical information with long‐term follow‐up. RESULTS In 612 prostate cancers, the overall rate of PTEN deletion was 112 (18.3%). Hemizygous PTEN losses were present in 55/612 (9.0%) of cancers, whereas homozygous PTEN deletion was observed in 57/612 (9.3%) of tumors. Significant associations were found between PTEN status and pathologic stage (P < 0.0001), seminal vesicle invasion (P = 0.0008), extracapsular extension (P < 0.0001), and Gleason score (P = 0.0002). In logistic regression analysis of clinical and pathological variables, PTEN deletion was significantly associated with extracapsular extension, seminal vesicle involvement, and higher Gleason score. In the 406 patients in which clinical information was available, PTEN homozygous (P = 0.009) deletion was associated with worse post‐operative recurrence‐free survival (number of events = 189), pre‐operative prostate specific antigen (PSA) (P < 0.001), and pathologic stage (P = 0.03). CONCLUSION PTEN status assessed by FISH is an independent predictor for recurrence‐free survival in multivariate models, as were seminal vesicle invasion, extracapsular extension, and Gleason score, and preoperative PSA. Furthermore, these data demonstrate that the assay can be readily introduced at first diagnosis in a cost effective manner analogous to the use of FISH for analysis of HER2/neu status in breast cancer. Combined with published research beginning 17 years ago, both the data and tools now exist to implement a PTEN assay in the clinic. Prostate 75: 1206–1215, 2015. © 2015 The Authors. The Prostate, published by Wiley Periodicals, Inc.